Climate Change and Food Security: Are Asian Economies Tracking Sustainable Development Goals? - Zahid, Fahmida; Hanif, Uzma; Javed, Faiza (iRASD Journal of Economics, 2022)
Sustainable Development Goals 2030 is a sustainable development track approved by the United Nations in 2015. All member countries are trying to attain these SDGs. Unfortunately, Asian countries are still far from this track. Achieving SDG 2 (zero hunger) under the shadow of climate change (SDG 13) requires an indispensable line of action for the developing world and, specifically, Asian countries. Food security is the first step to achieving SDG 2 with changing climate. This study investigates the probable footprints of climate change and other socioeconomic determinants on food security in 8 Asian food-insecure countries from 1990 to 2019. The study secrutinizes climate change and food security literature as they relate to an SDG-oriented policy agenda. The study results reveal that climate change and socioeconomic determinants substantially affect food security. The Panel Quantile Autoregressive Distributed Lag Model (PQARDL) outcomes illustrate that undernourishment prevalence (SDG 2.1.1) will likely be reduced due to increased agricultural productivity, food availability, and economic growth. However, this is compromised by the negative effects of greater variations in temperature and food supply. Increasing rainfall is likely to reduce the prevalence of undernourishment (SDG 2.1.1) in the long run. Contrarily, a temperature rise will exacerbate the prevalence of undernourishment (SDG 2.1.1). Based on the outcomes, comprehensive SDG-oriented policy recommendations have been put forward to realize the goals of SDG 2, SDG 8 and SDG 13 for Asian food-insecure countries.